The Effect of Destination Personality on Behavior Intention and Self Congruity as Intervening Variables - Eny Endah Pujiastuti; Didik Indarwanta; Aldy Ciptha Primanda (Journal of Business Innovation and Research, 2022)
Behavior intention has become a fundamental strategic metric to evaluate the success of tourist destinations. Behavior intention can be built through strong branding. Furthermore, the 2 elements of destination branding that can be used are destination personality and self-congruity. This study investigates: (1) Significant effect of destination personality on self-congruity. (2) significant effect of self congruity on behavior intention, (3) significant effect of destination personality on behavior intention, (4) significant effect of destination personality on behavior intention through self-congruity. Research conducted in tourist destinations Obelix Hills Yogyakarta. The sample criteria used were tourists who have never visited. Data collection using google form and 151 questionnaires were collected which were then processed using Structural Equating Modeling (SEM). This study found that (1) destination personality has a significant effect on self-congruity, (2) self-congruity has a significant effect on behavior intention, (3) destination personality has a significant effect on behavior intention, (4) destination personality has a significant effect on behavior intention through self-congruity. Destination Personality to be explored and highlighted in promoting the destination so that it can become a value for tourists.